2019
DOI: 10.4103/bc.bc_48_19
|View full text |Cite
|
Sign up to set email alerts
|

Infusion warm during selective hypothermia in acute ischemic stroke

Abstract: INTRODUCTION:Mechanical thrombectomy (MT) has dramatically improved the prognosis for acute ischemic stroke (AIS) patients. Despite high recanalization rates, up to half of the patients will not present a good neurological outcome after MT. Therapeutic hypothermia is perhaps the most robust neuroprotectant studied preclinically. MATERIALS AND METHODS:We explored various warming effects that can reduce the effectiveness or potency of selective hypothermia during AIS under conditions similar to actual clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This shortcoming inevitably causes the warming of the cold perfusate within the catheter as shown in Fig. 1 b [ 12 ] and reduces the potency of the hypothermia treatment for AIS [ 13 ]. For example, an in vitro phantom experiment indicated that the temperature of the 33 mL/min cold saline within the 5F interventional catheter increased from 5.4 ± 0.41 °C (at the initial femoral inflow site) to 25.21 ± 0.49 °C (at the distal tip of catheter in carotid artery) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shortcoming inevitably causes the warming of the cold perfusate within the catheter as shown in Fig. 1 b [ 12 ] and reduces the potency of the hypothermia treatment for AIS [ 13 ]. For example, an in vitro phantom experiment indicated that the temperature of the 33 mL/min cold saline within the 5F interventional catheter increased from 5.4 ± 0.41 °C (at the initial femoral inflow site) to 25.21 ± 0.49 °C (at the distal tip of catheter in carotid artery) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an in vitro phantom experiment indicated that the temperature of the 33 mL/min cold saline within the 5F interventional catheter increased from 5.4 ± 0.41 °C (at the initial femoral inflow site) to 25.21 ± 0.49 °C (at the distal tip of catheter in carotid artery) [ 14 ]. Current studies focus on making catheters with novel designs to improve their cooling performance by minimizing the heat exchange of the cold infusion fluid within catheter with the outside warm blood and tissues, such as balloon-wrapping [ 15 ], balloon-coaxial (TwinFlo @ ) [ 16 ] and coaxial configurations [ 13 ]. However, these cooling catheters are complicated to be manufactured and expensive, lack flexibility, and cannot be inserted into some target vessels due to their increased diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a phantom model constructed by Choi et al ( 69 ) showed that saline infused by a femoral catheter, running to the “internal carotid artery,” warmed to ~25°C at the catheter tip. Such warming is less likely to occur in animal studies of IA-SCI ( 69 , 71 ). These results are important for investigators to consider given the current methodology of ischemic stroke treatment and limitations with current medical equipment and experimental modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Open-loop, intra-arterial infusion of chilled saline can be easily incorporated into the workflow of endovascular thrombectomy procedures. However, the article by Merrill et al [17] shows that significant warming occurs when chilled saline passes through the tubes and then via uninsulated catheters into the carotid artery when it warms further as it mixes with the blood. The infusate volume required to produce brain cooling and the resulting hemodilution are also factors to be considered when employing this approach.…”
mentioning
confidence: 99%